Is there an association between the level of stress and the presence of musculoskeletal disorders in doctors? - Barahona Bustamante, Déborah Jael (2020)
Objective: To determine the association between perceived stress and the presence of musculoskeletal disorders in physicians at La Caleta de Chimbote Hospital and Eleazar Guzmán Barrón Regional Hospital in Ancash, Peru. Methods. An exploratory cross-sectional analytical study was conducted in 116 physicians. The Nordic Questionnaire was used to determine the areas of musculoskeletal pain and the Perceived Stress Scale (PSS-10) to assess the level of stress. The sociodemographic and occupational characteristics of the population were evaluated from the measurement of proportions and measures of central tendency and dispersion. For the bivariate analysis, Fisher's exact test and Chi2 were used. Finally, the multivariate analysis, based on a Logistics Regression model, was calculated with the crude and adjusted Odd Ratio (OR) [95% Confidence Intervals (CI)]. Results: The responses of 71 evaluations from a group of people between ages 34 to 59 (median 48) with a higher predominance of males (72%) were analyzed. No statistically significant association was found between the presence of non-specific musculoskeletal disorders and the perception of stress (p = 0.066); However, cervical, lumbar, hip / leg and ankle / foot pain specifically did show a significant association (p = 0.009; p = 0.033; p = 0.033 and p = 0.034, respectively). Finally, the cervical area maintained its association when performing the crude analysis and adjusted to physical activity (ORc = 7.29; 95% CI = 1.51-35.21 / ORa = 7.29 95% CI = 1.25-42.37). Anatomical areas such as lumbar, hip / leg and ankle / foot showed a non-significant association when performing the multivariate analysis.